Land Area Targets for Wind Energy: How Promising Is the New Onshore Wind Power Legislation? - Felix Reutter; Charlotte Geiger; Paul Lehmann; Jan-Niklas Meier; Philip Tafarte (Wirtschaftsdienst)
Abstract The expansion targets for onshore wind power have recently been more than tripled by the German government for the upcoming years. Meanwhile, the actual expansion of wind power in Germany has been stalled for several years. A major obstacle to expansion is that too few areas have been designated for wind turbines. To solve this problem, a new law has been passed, the “Windan-Land-Gesetz”. It sets explicit land area targets for the federal states to ensure that a total of 2 % of the national territory will be designated for wind turbines. This is a step in the right direction. However, it remains questionable whether the time-quantity framework is in line with national expansion targets.